The Impact of Service Recovery on Customer Satisfaction at PT Andalas Citra Elektrindo Medan - Erina Alimin; Eddy (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
The goal of service recovery is to address customer complaints, restore customer satisfaction and prevent customer exits. A successful service recovery has a positive impact on the overall satisfaction towards the company which ultimately leads to positive word-of-mouth and repeat purchase behaviour. After the service failure, service recovery should be done by the company in order to avoid the negative impacts of service failure on the customers. The process of service recovery is a part of quality management that intends to maintain business relationships with the customer. The process of service delivery has high chances to fail due to the presence of human element in it especially for company. The purpose of this research is to know whether service recovery has impact on customer satisfaction at PT Andalas Citra Elektrindo Medan. Research design used in this research is descriptive research design and correlational research design. Research methods which used are descriptive statistic analysis, validity and reliability test, normality test, coefficient correlation, coefficient of determinant, simple linear regression analysis and Z testing. The result of this research is the service recovery has impact on customer satisfaction at PT Andalas Citra Elektrindo. From Z test, it can be known that Zcount > Ztable. The coefficient of correlation value is 0.879. There is strong and positive relationship between service recovery and customer satisfaction in PT Andalas Citra Elektrindo. The coefficient of determination value is 77.2%. It means that 77.2% of customer satisfaction can be explained by service recovery in PT Andalas Citra Elektrindo. From result of regression analysis, it can obtain linear regression equation Y = 2.196 + 0.837 X. The increasing of 1 unit of the service recovery can make increasing of 0.837 unit of customer satisfaction. Most of respondent is disagree about the service recovery dimension in PT Andalas Citra Elektrindo. Most of respondent is disagree about the customer satisfaction dimension in PT Andalas Citra Elektrindo.